The Psychoactive Surveillance Consortium and Analysis Network (PSCAN): the first year. (25th November 2019) - Monte, Andrew A.; Hopkinson, Andrew; Saben, Jessica; Shelton, Shelby K.; Thornton, Stephen; Schneir, Aaron; Pomerleau, Adam; Hendrickson, Robert G.; Arens, Ann M.; Cole, Jon B.; Chenoweth, James; Martin, Spencer; et al.
Abstract : Background and aims: The Psychoactive Surveillance Consortium and Analysis Network (PSCAN) is a national network of academic emergency departments (ED), analytical toxicologists and pharmacologists that collects clinical data paired with biological samples to identify and improve treatments of medical conditions arising from use of new psychoactive substances (NPS). The aim of this study was to gather clinical data with paired drug identification from NPS users who presented to EDs within PSCAN during its first year (2016–17). Design: Observational study involving patient records and biological samples. Setting: Seven academic emergency medical centers across the United States. Participants: ED patients ( n  = 127) > 8 years of age with possible NPS use who were identified and enrolled in PSCAN by clinical providers or research personnel. Measurements: Clinical signs, symptoms and treatments were abstracted from the patients' health records. Biological samples were collected from leftover urine, serum and whole blood. Biological and drug samples, when available, were tested for drugs and drug metabolites via liquid chromatography–quadrupole time‐of‐flight mass spectrometry (LC‐QTOF/MS). Findings: Patients in whom synthetic opioids were detected ( n  = 9) showed higher rates of intubation (four of nine), impaired mental status (four of nine) and respiratory acidosis (five of nine) compared with the rest of the cohort (nine of 118, P ‐value < 0.05). Patients in whom synthetic cannabinoid (SC) were found ( n  = 27) had lower median diastolic blood pressures (70.5 versus 77 mmHg, P  = 0.046) compared with the rest of the cohort. In 64 cases of single drug ingestion, benzodiazepines were administered in 25 cases and considered effective by the treating physician in 21 (84%) cases. Conclusions: During its first year of operation, the Psychoactive Surveillance Consortium and Analysis Network captured clinical data on new classes of drugs paired with biological samples over a large geographical area in the United States. Synthetic cannabinoids were the most common new psychoactive drug identified. Synthetic opioids were associated with a high rate of intubation and respiratory acidosis.